Proiectul – metodă eficientă de colaborare în cadrul evaluării sumative [Articol] - Osoianu, Cătălina; Bîrnaz, Nina (CEP USM, 2024)
This article emphasizes the importance of the project as one of the effective methods for collaboration and relationships in summative assessment. Relationships within the group of students are facilitated by the quality of interrelationships in different educational contexts, and the summative assessment process can provide an excellent source of student expression and involvement. In this context, we reflect on the defining aspects of summative evaluation through the prism of the project, we valorize the steps that ensure the smooth running of the method, we present the criteria for project evaluation and a number of advantages of using the project as an evaluation method. Thus, in order to make the summative evaluation process more efficient, the application of the project method strengthens the balanced relationship between students and teacher.
PROJECT – AN EFFECTIVE METHOD OF COLLABORATION IN SUMMATIVE ASSESSMENT
Keywords: Effective communication; Project; Summative assessment